Construction of T-Nb2O5 nanoparticles on/in N-doped carbon hollow tubes for Li-ion hybrid supercapacitors. (10th January 2020) - Lian, Yue; Wang, Dawei; Hou, Shuangyue; Ban, Chaolei; Zhao, Jing; Zhang, Huaihao
Abstract: In recent years, hybrid supercapacitors (HSCs) with good characteristics of both lithium batteries (LIBs) and supercapacitors (SCs) have become a hot research topic to meet the growing market demand for electric and hybrid electric vehicles. The key for high-performance HSCs is the reaction kinetics imbalance between the slow faradaic intercalation anode and fast non-faradaic physical adsorption/desorption cathode. Herein, we simultaneously grow ultrafine Nb2 O5 nanoparticles on the inner walls and outer surface of hollow heteroatomic (N) carbon tube, giving a unique hierarchical hybrid nanostructure materials named T-Nb2 O5 @NC. The LIB test show its excellent high-rate capability and long-term cyclic stability. At current density of 0.25C (1.0–3.0 V, vs Li/Li + ), the reversible specific capacity of this material is up to 194 mAh g −1 . Importantly, the HSC device, assembled by T-Nb2 O5 @NC as anode and commercial activated carbon as cathode with an organic electrolyte, exhibits good electrochemical performance, including high energy density (49.7 Wh kg −1 ) and power density (8750 W kg −1 ), obviously superior to traditional HSC electrode materials. The results prove that T-Nb2 O5 @NC can be used as a promising HSC anode material. Graphical abstract: A hierarchical hybrid nanocomposite (T-Nb2 O5 @NC), T-Nb2 O5 nanoparticles growing on/in both sides of N-doped carbon hollow tubes with stabilized structures upon cycling, is a promising anode material for LIB and HSC. Image 1 Highlights: Nb2 O5 growing on both sides of N-doped carbon hollow tubes (inside and outside surface) relieve volume expansion and improve the rate performances. The T-Nb2 O5 @NC//AC HSC delivers high energy density of 49.7 Wh kg -1 at a power density of 8750 W kg -1 . N-doped carbon hollow tubes provides better electrochemical properties.